(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2024)
This article describes the main directions and practical measures to improve the mechanism of property relations. Improve the mechanism of property relations, strengthen the protection of property rights, free circulation of property and the development of a market economy, the introduction of innovations and digital transformation, improve educational and legal information on property rights, new modern technologies and qualified personnel. it is necessary to multiply, create new jobs, develop innovations, and highlights the views of economists on this matter, issues related to the main aspects of improving the mechanism of property relations.